PROSES PENGAWASAN OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI BANTEN DALAM PENYELENGGARAAN PENERIMAAN PESERTA DIDIK BARU (PPDB) JENJANG SEKOLAH MENENGAH ATAS - Muhamad Haykal Arraya Hibatullah; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The implementation of New Student Admissions (PPDB) for Senior High Schools is a form of public service in the field of education that has a high level of complexity and potential for maladministration. Various problems such as alleged extortion, quota discrepancies, excess capacity, and high public reports indicate the need for effective control process. This study aims to analyze the supervisory process of the Ombudsman of the Republic of Indonesia Representative of Banten Province in the implementation of PPDB for Senior High Schools, and to identify supporting and inhibiting factors in the supervisory process. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through in-depth interviews, observation, and documentation. Research informants consist of the Ombudsman of the Republic of Indonesia Representative of Banten Province, the Banten Provincial Education Office, and the community. Data analysis is carried out by referring to the supervisory process theory proposed by Robbins and Coulter, as well as supporting and inhibiting factors of control process according to T. Hani Handoko and Mulyadi. The results of the study indicate that the supervisory process of the Ombudsman of the Republic of Indonesia Representative of Banten Province has been implemented through standard setting, measuring actual performance, comparing implementation with standards, and taking action. The comparison phase of implementation against standards has been running optimally through identifying the causes of deviations. However, taking action cannot correct these deviations. Supporting factors for control process include the need for managers to delegate authority and changes in the organizational environment, while inhibiting factors include the complexity of actors and limited human resources in the implementation of PPDB.